A EUPHEMISM ANALYSIS IN THE 2024 INDONESIAN PRESIDENTIAL ELECTION DEBATE - Siahaan, Rachel Pratiwi; Bacas, Chintami Angelica; Daulay, Olga Adelia; Sembiring, Teresia Anjelina; Rangkuti, Rahmadsyah (Ma Chung Press, 2024)
This study analyzes the use of euphemisms in the debate of the 2024 Indonesian presidential candidates. Candidates used euphemisms to discuss sensitive issues such as corruption, human rights, and social inequality without causing conflict or harming certain parties. Using a qualitative approach, data were taken from the transcript of the debate broadcast on the official YouTube channel of the Indonesian General Elections Commission (KPU RI). The euphemisms presented were based on Warren’s theory (1992), including derivation, compounding, and blending. The results showed that 15 euphemisms were identified from the debate; 8 derivations, 5 compoundings, and 2 blends, of which derivation was the most dominant euphemism. Euphemisms helped candidates convey criticism and sensitive issues more subtly, maintain their public image, and create a more friendly and non-confrontational debate atmosphere. Euphemisms are essential in political communication, especially in Indonesian culture, which priorities gentle and indirect communication. This study contributes to understanding how language can be used to influence public perception and voter decision-making in important political events.